A Paper‐Based Potentiometric Sensor for Solid Samples: Corrosion Evaluation of Reinforcements Embedded in Concrete Structures as a Case Study. Issue 10 (20th May 2020) - Colozza, Noemi; Sassolini, Alessandro; Agosta, Lorenzo; Bonfanti, Alfredo; Hermansson, Kersti; Arduini, Fabiana
Abstract: Herein, we present the first paper‐based device for facing one of the worldwide concerns of the Modern age: the corrosion‐induced deterioration of reinforced concrete. Indeed, the monitoring of corrosion extent in reinforced concrete constructions has been acknowledged as a priority for public safety. In this work, the porosity properties of a paper‐based screen‐printed Ag/AgCl electrode were exploited for realising a smart analytical tool to be directly applied on the solid surface of concrete for the evaluation of corrosion. The analysis was carried out by measuring the electrochemical potential between the metallic reinforcement and the sensor, needing only 70 μL of electrolyte solution. The sensor was firstly tested in the laboratory using reinforced concrete samples and then applied on the real outdoor artwork Music Collection Session by Arman (Milan, Italy). A summary of the main available non‐destructive techniques for corrosion monitoring is reported to provide a critic overview. Abstract : Protect the arts : A paper‐based screen‐printed Ag/AgCl electrode was developed for the monitoring of the corrosion extent of the metallic components used into reinforced concrete, by real‐time potentiometric measurements (time of analysis of 30 s). The sensor was suitable to be applied directly on the solid surface of concrete by using only 70 μL of electrolyte. On site analysis were carried out on a real artwork to show the applicability of this analytical tool.